Patrimônio e identidade cultural, a distopia entre o institucional e o real : o caso do projeto construindo a cidade - Campos, Tiago de (2022)
The legitimation of the heritage of cities, which obeys the precepts of institutionality, prevails in contemporary urbanism, without considering where, from whom and for whom they were and are made. This research intends to take a look at the space and symbolism of the iconic aspects of a community located in Brazil, in the state of Rio Grande do Sul, in the city of Camaquã, based on the documentary review of reports from the heritage education project “Construindo a Cidade ”, based on the concept of cultural identity developed by Paulo Freire and on the Lefebvrian perspective of inhabiting. The aim of this analysis is to question the symbolic value of the different urban spaces established by the traditional and official conception of this locus, in contrast to the vivacity of the perception of the popular communities that inhabit the place in question, which led to the realization of the role of the State in the systematic erasure of popular symbols and their function for the maintenance of bourgeois ideology.